2011
DOI: 10.1021/ma200362u
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Based and Organic-Phase-Based AGET ATRP PolyHIPE Synthesis within Pickering HIPEs and Surfactant-Stabilized HIPEs

Abstract: PolyHIPEs are porous polymers synthesized within high internal phase emulsions (HIPEs). Recent research has shown that the locus of conventional free radical initiation (at the oil–water interface or in the organic phase) can affect the polyHIPE’s structure and properties. This paper is the first investigation of polyHIPE synthesis using activators generated by electron transfer for atom-transfer radical polymerization (AGET ATRP). Two different types of initiators (organic-phase-based and nanoparticle-based) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 67 publications
6
96
0
Order By: Relevance
“…This is supported by the TEM images and a recent study demonstrating the efficient self-assembly of nanoparticles in the range of 5-10 nm at polyHIPE pore walls. 30,42 Recent scouting studies with smaller MgOH nanoparticles (5-20 nm) in these polyHIPEs have confirmed our hypothesis that smaller particles can selfassemble and pack at the pore surface. Notably for this work, alizarin red staining of calcium ions on polyHIPEs with ACP and HA illustrated the presence of these particles at the surface (Fig.…”
Section: Incorporating Cap and Dbm Particles Into Polyhipessupporting
confidence: 70%
“…This is supported by the TEM images and a recent study demonstrating the efficient self-assembly of nanoparticles in the range of 5-10 nm at polyHIPE pore walls. 30,42 Recent scouting studies with smaller MgOH nanoparticles (5-20 nm) in these polyHIPEs have confirmed our hypothesis that smaller particles can selfassemble and pack at the pore surface. Notably for this work, alizarin red staining of calcium ions on polyHIPEs with ACP and HA illustrated the presence of these particles at the surface (Fig.…”
Section: Incorporating Cap and Dbm Particles Into Polyhipessupporting
confidence: 70%
“…Pickering HIPEs, HIPEs stabilized using either inorganic or polymeric amphiphilic nanoparticles (NPs), have also been developed. One advantage of Pickering HIPEs is the relatively high stabilization efficiencies exhibited at relatively low NP concentrations . Stabilizing NPs that are functionalized can also play critical roles in the polymerization reaction (the NPs can bear initiation sites) and in defining the macromolecular structure (the NPs can bear crosslinking sites).…”
Section: Emulsion Templating: Space – the Porous Frontiermentioning
confidence: 99%
“…2020, 60, 140 -150 is the relatively high stabilization efficiencies exhibited at relatively low NP concentrations. [66,[85][86][87][88][89][90] Stabilizing NPs that are functionalized can also play critical roles in the polymerization reaction (the NPs can bear initiation sites) and in defining the macromolecular structure (the NPs can bear crosslinking sites). The presence of an internal phase and the use of a stabilization system thus provide additional factors that can be used to enable the generation of novel porous polymer systems.…”
Section: Essaysmentioning
confidence: 99%
“…The effect of the locus of initiation on pore interconnectivity has been noted previously in the polyHIPE literature. [33][34][35][36] However, a mechanistic understanding of the process has yet to be discussed. A probable description of interconnect formation based on the forces generated during the conversion from PFDMA macromer to cross-linked polymer is illustrated in Figure 3.…”
Section: Locus Of Initiationmentioning
confidence: 99%
“…Recently, the Silverstein group published studies describing the effect of the locus of initiation on pore architecture and properties. [33][34][35][36] The authors proposed that organic-phase initiation resulted in larger, spherical, interconnected pores and an increased loss modulus relative to aqueous-phase initiation. 34 However, a mechanistic description of the effect of locus of initiation on the resulting macromer densification forces and the corollary effect on interconnect formation was not described.…”
Section: Introductionmentioning
confidence: 99%